The will to knowledge in the story of Hayy bin Yaqzan according to Ibn Sina and Ibn Tufayl. (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This research is concerned with analyzing the philosophical problems raised by the story of “Hayy ibn Yaqzan,” which was written by the philosopher Ibn Sina and reproduced by the philosopher Ibn Tufayl. It is also concerned with clarifying the tools of the perceiving self, perceives its existence and its surroundings in the cognitive journey that the two stories describe in a linguistic style that adopts strangeness, symbolism, and representing the truth without declaring it. The research seeks to monitor the will to knowledge, the existential experience, and the meditative and interpretive path of the human being searching for truth, starting with his awareness of himself and his cognitive powers, all the way to the perception of the intelligible world. It also seeks to analyze the method of pointing and warning that the two philosophers followed in their stories to express the alienation of philosophical discourse in the society of Arab-Islamic civilization in the middle Ages.